Experimental investigation of mid-infrared Er:ZBLAN fiber laser - Pajewski, Łukasz; Sójka, Łukasz; Lamrini, Samir; Benson, Trevor; Seddon, Angela; Sujecki, Sławomir (Photonics Letters of Poland, 2020)
In this contribution the diode pumped high-power Er:ZBLAN laser operating at around 2.8 µm is reported. The laser produces 2 W output power with the slope efficiency of 24 % measured with respect to the incident pump power. Full Text: PDF References S. D. Jackson, "Towards high-power mid-infrared emission from a fibre laser", Nature Photonics 6, 423 (2012). CrossRef V. Portosi, D. Laneve, C. M. Falconi, and F. Prudenzano, "Advances on Photonic Crystal Fiber Sensors and Applications", Sensors 19, (2019). CrossRef M. C. Falconi, D. Laneve, and F. Prudenzano, "Advances in Mid-IR Fiber Lasers: Tellurite, Fluoride and Chalcogenide", Fibers 5, 23 (2017). CrossRef M. Michalska, P. Grześ, J. Świderski, "High power, 100 W-class, thulium-doped all-fiber lasers", Phot. Lett. Poland, 11, 109 (2019). CrossRef Y. O. Aydin, V. Fortin, R. Vallée, and M. Bernier, "Towards power scaling of 2.8 μm fiber lasers", Opt. Lett. 43, 4542 (2018). CrossRef S. Crawford, D. D. Hudson, and S. D. Jackson, "High-Power Broadly Tunable 3- μm Fiber Laser for the Measurement of Optical Fiber Loss", IEEE Photonics Journal 7, 1 (2015). CrossRef V. Fortin, F. Jobin, M. Larose, M. Bernier, and R. Vallée, "10-W-level monolithic dysprosium-doped fiber laser at 3.24 μm", Opt. Lett. 44, 491 (2019). CrossRef L. Sójka, et al., "Experimental Investigation of Mid-Infrared Laser Action From Dy3+ Doped Fluorozirconate Fiber", IEEE Photon. Technol. Lett. 30, 1083 (2018). CrossRef M. Pollnan and S. D. Jackson, "Erbium 3 /spl mu/m fiber lasers", IEEE J. Sel. Top. in Quantum Electron., 7, 30 (2001). CrossRef Y. O. Aydin, F. Maes, V. Fortin, S. T. Bah, R. Vallée, and M. Bernier, "Endcapping of high-power 3 µm fiber lasers", Opt. Express 27, 20659 (2019). CrossRef C. A. Schäfer, "Fluoride-fiber-based side-pump coupler for high-power fiber lasers at 2.8 μm", et al., Opt. Lett. 43, 2340 (2018). CrossRef O. Henderson-Sapir, J. Munch, and D. J. Ottaway, "New energy-transfer upconversion process in Er3+:ZBLAN mid-infrared fiber lasers", Opt. Express 24, 6869 (2016). CrossRef F. Maes, V. Fortin, S. Poulain, M. Poulain, J.-Y. Carrée, M. Bernier, and R. Vallée, "Room-temperature fiber laser at 3.92 μm", Optica 5, 761 (2018). CrossRef R. I. Woodward, M. R. Majewski, D. D. Hudson, and S. D. Jackson, "Swept-wavelength mid-infrared fiber laser for real-time ammonia gas sensing", APL Photonics 4, 020801 (2019). CrossRef M. Kochanowicz, et al., "Near-IR and mid-IR luminescence and energy transfer in fluoroindate glasses co-doped with Er3+/Tm3+", Opt. Mater. Express 9, 4772 (2019). CrossRef M. Kochanowicz, et al., "Sensitization of Ho3+ - doped fluoroindate glasses for near and mid-infrared emission", Optical Materials 101, 109707 (2020). CrossRef J. Wang, X. Zhu, M. Mollaee, J. Zong, and N. Peyhambarian, "Efficient energy transfer from Er3+ to Ho3+ and Dy3+ in ZBLAN glass", Opt. Express 28, 5189 (2020). CrossRef M. C. Falconi, D. Laneve, V. Portosi, S. Taccheo, and F. Prudenzano, "Design of a Multi-Wavelength Fiber Laser Based on Tm:Er:Yb:Ho Co-Doped Germanate Glass", J Lightwave Technol 1 (2020). CrossRef K. Anders, A. Jusza, P. Komorowski, P. Andrejuk, and R. Piramidowicz, "Short wavelength up-converted emission studies in Er3+ and Yb3+ doped ZBLAN glasses", J. Lumin. 201, 427 (2018). CrossRef P. Komorowski ,K. Anders ,U. Zdulska,R. Piramidowicz R. "Erbium doped ZBLAN fiber laser operating in the visible - feasibility study", Photonics Lett Pol 9, 85 (2017). CrossRef J. Swiderski, M. Michalska, and P. Grzes, "Broadband and top-flat mid-infrared supercontinuum generation with 3.52 W time-averaged power in a ZBLAN fiber directly pumped by a 2-µm mode-locked fiber laser and amplifier", Applied Physics B 124, 152 (2018). CrossRef V. Fortin, M. Bernier, S. T. Bah, and R. Vallée, "30 W fluoride glass all-fiber laser at 2.94 μm", Opt. Lett. 40, 2882 (2015). CrossRef